The shifting patterns of childhood obesity: Insights from national school screening data - Arwa Alhamed; Abdullah Al-Zeer; Fahad Alsaawi; Abdulrahman Alshaikh; Abrar Alzaher; Abdullah Alkattan; Noura Alrasheed; Khlood Sagor; Elham Alsalem; Mona Ibrahim; Amjad Alfaleh (Elsevier, 2023)
Background: Recent reports indicated an increasing prevalence of obesity among children and adolescents in Saudi Arabia, making it an impending national epidemic. However, obesity prevalence data in children and adolescents in Saudi Arabia are largely inconsistent. Objectives: This study analyzed and compared the prevalence of obesity among a national sample of children and adolescents across sexes, school grades, regions, and city types in Saudi Arabia using the Growth Charts for Saudi Children and Adolescents. Methods: Weight, height, and body mass index (BMI) data from 1 134 317 children in first, fourth, seventh, and tenth school grades who participated in the national school screening program were analyzed cross-sectionally. BMI values were classified using the Growth Charts for Saudi Children and Adolescents. Results: Nearly 10.4% of students were overweight, 10.7 % were obese, and 4.50% were severely obese. Male students had a higher prevalence of overweight and obesity than their female counterparts. The prevalence of overweight and obesity was the highest among students in intermediate school, the Central region, and administrative capitals. Conclusion: Managing childhood obesity is challenging due to its multifaceted nature Therefore, utilizing clinical and community-based participatory approaches is essential to develop nationwide obesity prevention and management program that is effective and sustainable. This program must utilize dynamic BMI surveillance systems using ethnically representative growth references, conduct national pediatric obesity research with careful consideration for demographic and regional differences, lead targeted pediatric obesity awareness campaigns, provide obesity management interventions in a pediatric multi-disciplinary clinic, and evaluate the program outcomes periodically.